(3GdeYJHQ aj GdMceIs - (3gHI Gddg Hf Ydj Hf edcG GdHdOj, CHh GdHQcGJ,J (B560 (3g` s ((3gHI Gddg Hf eMeO Hf Ydi Hf GdMSf GdbQTi s)
(3ChdgG (B:s
[(3GdYde GdEdgi(B] s
(3BNQgG (B:s
(3BNQ GdcJGH s
(3GdfSNI HgG MhGTs
(3eLdOI efgs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B74s
Keywords: (3GdadSaI hGdefWbs